A Clinical Trial of a Microcrystalline Cellulose Topical Nasal Spray on the Acute Response to Allergen Challenge. Issue 4 (July 2016) - Lansberg, Marianella Paz; DeTineo, Marcy; Lane, James; Pinto, Jayant M.; Baroody, Fuad M.; Naclerio, Robert M.
Background: Allergic rhinitis is a common disorder that leads to a negative impact on quality of life. Multiple options are available for treatment of the symptoms, but preventing the reaction should be an effective strategy. Objective: We tested a nasal spray that contained microcrystalline cellulose designed to limit airborne allergens from penetrating the nasal mucosa (nasal blocker) and, therefore, prevent the initiation of the allergic reaction. Methods: We performed a randomized, double-blind, placebo-controlled, two-way crossover clinical trial with 20 subjects who had a history of seasonal grass and/or ragweed allergy symptoms. Each subject underwent two separate nasal challenges with antigen (provocations) after application of the investigational product or placebo to both nostrils. The allergen was delivered into one nostril at a time and was administered at 2-hour intervals (identified as challenge 1 and challenge 2). We assessed peak nasal inspiratory flow and total nasal symptoms as well as the number of sneezes recorded at both 15-minute and 1-hour intervals after challenge 1 and, later, challenge 2. After a washout period, the subjects returned to undergo the alternate therapy. Results: There was a significant overall decrease in peak nasal inspiratory flow after both treatments (investigational product, p = 0.005; placebo, p = 0.001), but, when the average of the change from baseline in peak nasal inspiratory flow was compared with the baseline, the results showed no significant differences between the groups (p = 0.31). Similar results were obtained for total nasal symptoms. Conclusion: The investigational product did not prove to be significantly better than placebo in treating seasonal allergic rhinitis symptoms.